1979
DOI: 10.2307/1239448
|View full text |Cite
|
Sign up to set email alerts
|

The Factor Share Approach to Production Function “Estimation”: Actual or Estimated Equilibrium Shares?

Abstract: For years agricultural economists have been concerned with obtaining reliable estimates of production function parameters. Among other reasons, such estimates are needed to address policy issues involving resource misallocation, supply response, and factor demand in agriculture. The appeal of production function approaches to such problems, as contrasted with direct estimation of product supply and factor demand relationships, is with the richness of the model for addressing cross-price effects and matters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…However, the convention of deriving the output elasticity of labor as a residual means that only seven of the estimates are independent." More recently, Shumway et al (1979) have provided additional support for the factor shares approach. Griliches (1964, p. 970) found that observed factor shares in V.S.…”
Section: Estimation Ofoutput Elasticitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the convention of deriving the output elasticity of labor as a residual means that only seven of the estimates are independent." More recently, Shumway et al (1979) have provided additional support for the factor shares approach. Griliches (1964, p. 970) found that observed factor shares in V.S.…”
Section: Estimation Ofoutput Elasticitiesmentioning
confidence: 99%
“…Lyu et al (1984) and Chambers and Lee have concluded that slight decreasing returns to scale may in fact be the case. Peterson (1967), Bredahl and Peterson ( 1976) and Shumway et al ( 1979) have employed the Cobb-Douglas functional form with success. These results are taken as the empirical rationale for the maintained hypothesis of constant returns to scale in the production functions for the crop and livestock sectors.…”
Section: Estimation Ofoutput Elasticitiesmentioning
confidence: 99%
“…agriculture between 1949 and 1959 were statistically indistinguishable from those deduced from his estimated production function. More recently, Shumway et al (1979) have provided additional support for the factor shares approach.…”
Section: Estimation Ofoutput Elasticitiesmentioning
confidence: 99%
“…962-964) was unable to reject the hypothesis of an elasticity of substitution of 1.0. Peterson (1967), Bredahl and Peterson ( 1976) and Shumway et al ( 1979) have employed the Cobb-Douglas functional form with success. Third, while there seems to be some agreement on the economies of scale question, and on the matter of the choice of functional form, very little consensus has been achieved on the value of particular output elasticities.…”
Section: Estimation Ofoutput Elasticitiesmentioning
confidence: 99%
“…Three methods for estimating input shares have been used in past studies and all three are used here: the non-normalised gross output method, the normalised gross output method (normalised over capital inputs and labour only) and the total expenditure method (normalised over all inputs). Discussions of these methods can be found in Tyner and Tweeten (1965), Rayner (19706), Young (1971), Rosine and Helmberger (1974), Shumway et al (1979) and Pandey (1981).…”
mentioning
confidence: 99%